-6(x-6)=3(0+x)

Simple and best practice solution for -6(x-6)=3(0+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x-6)=3(0+x) equation:


Simplifying
-6(x + -6) = 3(0 + x)

Reorder the terms:
-6(-6 + x) = 3(0 + x)
(-6 * -6 + x * -6) = 3(0 + x)
(36 + -6x) = 3(0 + x)
Remove the zero:
36 + -6x = 3(x)

Solving
36 + -6x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
36 + -6x + -3x = 3x + -3x

Combine like terms: -6x + -3x = -9x
36 + -9x = 3x + -3x

Combine like terms: 3x + -3x = 0
36 + -9x = 0

Add '-36' to each side of the equation.
36 + -36 + -9x = 0 + -36

Combine like terms: 36 + -36 = 0
0 + -9x = 0 + -36
-9x = 0 + -36

Combine like terms: 0 + -36 = -36
-9x = -36

Divide each side by '-9'.
x = 4

Simplifying
x = 4

See similar equations:

| 0.5=0.4 | | R+2-3=4 | | x+(x-20)=78 | | 11x-7(-4+2x)=-14 | | 7x+3=56 | | -4x^2-5.5x+5=0 | | -5x-4(-3x+15)=3 | | -6(-v-3y+4)= | | 2x^2-4x+4=25 | | 0.8x-4=1.5x+0.2 | | 48.15/45 | | 0.8x-4=1.5+0.2 | | f(x)=x^4+8x^2-12 | | x^2-2x=10.5 | | 3x+4(-4x+16)=8 | | 3x+10=2x+x+18 | | 4+33x=95 | | xsquared-2x=10.5 | | -2x+4x=56 | | -29+(-25)= | | 3(2u+7)=-12+8u | | 85/5= | | 7(2x-5)=4(6x-2)+x | | 2/3m-10=-12 | | 3x^2+81x-972=0 | | 10x+30=10x+60 | | 3(t)+1(n)=9 | | x+3(-10)=-9 | | 5(t)+3(n)=19 | | W/2-3=8 | | W/2-3=- | | -2x-10-2x=2(x+4) |

Equations solver categories